Racialidades e a produção de artigos científicos no conhecimento geográfico brasileiro entre 2001 e 2018. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This investigation aims to understand how the dynamics of racialities permeated the production of scientific papers in the Brazilian geography between 2001 and 2018. To develop the study, 98 online journals that are part of the Geography area of the QualisCAPES system were surveyed, which resulted in 25.437 papers. Out of that number, 452 papers were selected for being related to the theme of racialities. In addition, 7 interviews were carried out, the interviewees were 03 men and 04 women that are teachers in higher education institutions and belong to the group called black geographers. The content of the papers and the interviews were systematized using content analysis, as suggested by Bardin (2002), and Silva and Silva (2016). The results of our analysis showed that the field of racialilies in the Brazilian Geography corresponds to only 1.8% of the whole production. Hegemonic themes that support this production are traditional communities, indigenous and quilombolas, which are always treated as collectives or groups, and the territory is their basis. The hegemony of male authorship regarding academic productivity and legitimacy is clear, and the trajectories of the researchers interviewed revealed limitations imposed to racialilites in the Brazilian geographical debate.
Keywords: Produção científica; Racialidades; Geografia brasileira; Epistemologia; Scientific Production; Racialities; Brazilian Geography; Epistemology; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS